The effect of live-performed music therapy with physical contact in preterm infants on parental perceived stress and salivary cortisol levels - Dewan, Monia Vanessa; Ader, Miriam; Kleinbeck, Tim; Dathe, Anne-Kathrin; Schedlowski, Manfred; Engler, Harald; Felderhoff-Mueser, Ursula; Bruns, Nora; Kobus, Susann (Frontiers in Psychology, 2024)
Introduction Parents of preterm infants face a stressful life event which might have long term impact on the parent–child relation as well as on the infant’s cognitive and socio-emotional development. Both music therapy (MT) and physical contact (PC) are stress-reducing interventions for parents and preterm infants on the neonatal intensive care unit (NICU). Meanwhile, especially close PC is considered as standard care (SC) in most NICUs. However, the effect of live performed MT with PC on parental perceived stress and cortisol levels has barely been investigated. We hypothesized that MT with PC leads to reduced stress levels and lower salivary cortisol concentrations compared to SC in parents of preterm infants during the first 4 weeks after birth. Methods Randomized-controlled trial enrolling the parents of 99 preterm infants (MT n = 50, SC n = 49 infants). The infants received either MT with PC or SC only. Perceived stress was measured with the perceived stress questionnaire 20 (PSQ-20) after birth and 4 weeks later. Salivary cortisol levels were obtained and measured weekly after birth for 4 weeks. Results Forty-two mothers and eight fathers of the intervention group (MT with PC) as well as n = 43 mothers and n = 6 fathers of the control group (SC) were enrolled. For the intervention group, salivary cortisol was reduced 4 weeks after birth [mothers 5.5 nmol/l (confidence interval (CI) 3.6–7.5); fathers 8.3 (CI 7.2–9.4)] compared to the control group [mothers 10.3 nmol/l (CI 5.4–15.3); fathers 14.8 (CI 8.9–20.7)]. Overall perceived stress scores decreased in the intervention group (mothers −17.6; fathers −12.6) and increased in the control group (mothers +6.1; fathers +21.4) over 4 weeks. Discussion Live-performed MT with PC in preterm infants might be an effective, non-invasive intervention to reduce parental stress and cortisol levels. Future studies should investigate the long-term effects of this intervention on the parent-infant relation as well as on the infants’ cognitive and socio-emotional development. Clinical trial registration https://drks.de/search/en/trial/DRKS00025755 identifier [DRKS00025755].